Identidades goianas no ensino fundamental de geografia - BORGES, Joyce de Almeida (2010)
This dissertation has the goal of discussing how the goiana identities materialize themselves in the Geography education in Goiânia, and to analyze how the students conceive what is to be goiano and what makes part of their identities. One of the procedures consisted in observation of how these students assimilate the identity speeches built by the State, media and education. We identified how this trinity reflects in the identity speeches construction having as reference the students and teachers perception. Firstly it was identified how the books do not point the referred themes neither the goiana cultural reality in their geographic interpretations. Teachers and students gave testimonials about this reality in the Geography education. The methodological procedures used to the dissertation accomplishment were reading, direct techniques to the field, interviews, questionnaires, mental maps, reports and photos. The results achieved by the interviews and observations demonstrated that the goiana identities are partially approached themes in the geography education in Goiânia and that the teachers face difficulties in materializing the thematic in the classroom. Furthermore, we verified that the students still have goiana culture representation associated to the stereotypes preached by the media and by the State